Resolusi Konflik Pembangunan Pasar Desa Sumowono, Kecamatan Sumowono, Kabupaten Semarang - Lailiya Nuriya Ulfa; Turtiantoro . (Journal of Politic and Government Studies, 2020)
This research concerns about development process of the SumowonoVillage Government Market which is interesting to discuss further because in theprocess various problems or more specifically conflict occur. Conflicts occurred atthe beginning of market development by the Sumowono Village Government. In theinitial stages of the eviction of the stalls located on the village land, it involvedprotests by traders who used the stalls, causing conflicts and hampering the villagemarket development process. This study is intended to examine further the caserelated to Conflict Resolution of Village Market Development in SumowonoVillage, Sumowono District, Semarang Regency. The method used is descriptive qualitative method by collecting datathrough interviews and documentation. This study is guided by key questions toanswer the question "Why did conflict occur in the development of the SumowonoVillage Market, how was it resolved, and howwas the role of a third party in helpingto resolve the conflict?".Based on the results of the study it was found that the cause of dissent in theconstruction of the Sumowono Village Market between the Government of theSumowono Village with the traders who previously owned government-owned landin the management of the Semarang Regency Trade Office. The resolution of theconflict was resolved with the of a third party, the Semarang Regency Government.Keywords: Conflict, Development, Village Market, Resolution